Possibility of Adopting Integrated Business Reports as a Tool for Accounting Disclosure Environmental Activities: An Empirical Study on the Companies Subordinate to National Oil Establishment - الفضلي , خالد; بن مراد, فاطمة (Dirasat in Economics and Business, 2020)
Some of prior studies, conducted within Libyan environment, suggest that oil companies unable of disclose environmental information in its regular financial reports. They also do not have accepted environmental disclosure requirements. Thus, integrated business report considered a modern disclosure tool capable of achieving integration and balance of disclosure. The use of such report can combines both financial and non-financial information. Therefore, the current study aims to identify these companies' ability to adopt integrated business report as a tool of accounting disclosure of environmental activities. For the study purpose, we relied on studying several cases as a technique of research, as it is an ideal method to understand the various aspects of the study problem. Interviewing financial reports makers, however, was the main instrument of gathering the basic data. The number of interviews was fifteen from three oil companies subordinate to national oil establishment. The study depended on descriptive statistics for data analysis. It concluded that the percentage of adopting integrated business report so low, it amounts to 50 and 61 per cent for financial and nonfinancial disclosures, respectively. This low degree is due to many reasons including the company's disinterest of disclosing their environmental activeities, lack of the rules that bend companies to disclose such activities, unawareness of report makers of international criteria and accounting releases concerning environmental disclosure. The study recommended conducting further research on environmental activities via integrated business report using ways and means of collecting more data that may contribute to increase the knowledge of this topic.